A judicialização do direito à educação - o olhar do tribunal de justiça do estado do Rio Grande do Sul - Maito, Maríndia Catto (2017)
The right to education is seen, in Brazil, in the set of social rights, originally welcomed as the right of all and the duty of the State. Faced with this, we present the school relations that flow into the Judiciary through the increasing judicial interventions that are established between the law and Education, and also counts on the consequent mediation of the Public Ministry in educational matters. In this paper, we seek to raise hypotheses about the considerable increase in judicial demands as a solution strategy to achieve one of the main fundamental rights of citizens, provided for by the Federal Constitution of 1988 in its articles 6, 205 and 208, which is the right to Education. It occurs that the judicialization of Education represents the search for more and better instruments for the defense of legally protected rights, since access to justice has come to be recognized as a guarantee of the exercise of citizenship. This study was based on a documentary research in the electronic archives made available by the website of the South-Riograndense Court of Justice, and, methodologically, the study was carried out by qualitative descriptive-interpretative research, with a bibliographical contribution, aiming to investigate the discussion about the judicialization of Education as a strategy for the implementation of the Right to Public Education, analyzing the literature on the subject and the decisions handed down by the High Court of Justice of the State of Rio Grande do Sul. The research was based on the following authors: CURY, 2008; 2010; 2016; BOAVENTURA, 1977; 1997; 1998; 1999; DINIZ, 1999. It is concluded with this research that the Right to Education is also guaranteed by the Judiciary and related, because, for the realization of social rights to be given through public policies, the great challenge has been to establish mechanisms to ensure enforceability and judicial control of compliance in case of absence or insufficiency of the policies adopted. One of the possibilities to assert this right is to resort to the justice system, either through the performance of the Judiciary or the Public Ministry and their respective competent bodies.